2016
DOI: 10.1148/radiol.2015142899
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Xenografts: Use of VEGFR2-targeted Microbubbles for Combined Functional and Molecular US to Monitor Antiangiogenic Therapy Effects

Abstract: Purpose-To assess the ability of vascular endothelial growth factor receptor type 2 (VEGFR2)-targeted and nontargeted ultrasonography (US) to depict antiangiogenic therapy effects and to investigate whether first-pass kinetics obtained with VEGFR2-targeted microbubbles provide independent data about tumor vascularization. Materials and Methods-Governmental approval was obtained for animal experiments.Vascularization in response to anti-vascular endothelial growth factor receptor or vehicle-control treatment (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
(55 reference statements)
1
24
0
Order By: Relevance
“…This is in accordance with Baetke et al, who showed in their study with heterotopic squamous cell carcinoma xenografts in nude mice under anti-VEGF antibody therapy 8 minutes after BR55 MB injection a significant lower amount of specifically bound BR55 MB in treated tumors compared to the control group on day 4, day 7 and day 14 [21]. Corresponding to our results, Pysz et al reported a significant difference of targeted imaging signal using CEUS and BR55 already 24h after initiation of anti-VEGF-antibody therapy in human colon cancer xenografts in mice, which remained significantly lower in treated than in untreated animals during 5 days of observation [10].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in accordance with Baetke et al, who showed in their study with heterotopic squamous cell carcinoma xenografts in nude mice under anti-VEGF antibody therapy 8 minutes after BR55 MB injection a significant lower amount of specifically bound BR55 MB in treated tumors compared to the control group on day 4, day 7 and day 14 [21]. Corresponding to our results, Pysz et al reported a significant difference of targeted imaging signal using CEUS and BR55 already 24h after initiation of anti-VEGF-antibody therapy in human colon cancer xenografts in mice, which remained significantly lower in treated than in untreated animals during 5 days of observation [10].…”
Section: Discussionsupporting
confidence: 91%
“…Multiparametric CEUS with targeted microbubbles (MB) can characterize morphological, functional and molecular parameters of tumor pathophysiology from its earliest stages [916]. Preclinical and clinical studies demonstrated the feasibility of functional and molecular CEUS imaging with VEGFR2 (vascular endothelial growth factor receptor 2) targeted MB in monitoring therapy response to anti-angiogenic treatment in different tumor entities [11,1721], as VEGF is one of the most potent growth factors of endothelial cells and a main regulator of angiogenesis [2224]. Following intravenous injection, in a first early phase tumor perfusion can be quantitatively evaluated by the assessment of various parameters of tissue microcirculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, DCE-US has been increasingly investigated in preclinical [24,26,27] and clinical [28,29] studies to depict therapy induced changes in tumor perfusion. However, a major drawback of conventional DCE-US to date is its limitation to 2D, which results in limited perfusion assessments to a single 2D plane, and results in longitudinal sampling errors.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of intravenous microbubble US contrast agents, functional imaging of tumor perfusion, also called dynamic contrast material–enhanced ( DCE ) US, has become clinically available (3). However, DCE US with current two-dimensional imaging capabilities is suboptimal because it fails to demonstrate the spatial heterogeneity of tumor perfusion, and it is challenging to position the two-dimensional US transducer at the exact same location for longitudinal assessment of tumor response (48). This limitation has been addressed by the introduction of three-dimensional (3D) DCE US techniques (911).…”
mentioning
confidence: 99%